A study on awareness of disaster risk reduction (DRR) among university students: the case of PETRONAS residential hall students - Abdul Nifa, Faizatul Akmar; Chong, Khai Lin; Wan Mohd Rani, Wan Nurul Mardiah; Ooi, Jun Wei (IP Publishing LLC, 2018)
Over a past few decades, the topic on disasters is always been discussed around the world until today. Disasters are not natural in some cases. It can be prevented before a hazard resulted into a destructive disaster. As we can see within this few years, the disasters are happening widely around Malaysia, such as the floods during the Northeast Monsoon season. The awareness of people must be raised to enhance and increase the knowledge and information on disasters. This study focusses on the level of knowledge on Disaster Risk Reduction (DRR) among PETRONAS students in order to increase the understanding regarding DRR and explore a method to come out with a suitable program that can enhance the awareness of DRR in UUM. Data gathered from 235 DPP PETRONAS students from different college via a questionnaire survey and the result is test by SPSS v.24 statistical technique. The reliability analysis revealed that there was significant among 14 items which has been test, Cronbach’s Alpha = 0.834. Since this is a preliminary study on awareness of DRR among students in DPP PETRONAS, further research can be done within a larger scope of population to enhance the result of the study.